Examination of Knowledge and Fear Levels of Breast Cancer With the Spiritual Characteristics of Nurses - Cal, Ayse; Kabatas Yildiz, Mukerrem; Aydin Avci, Ilknur (Frontiers in Public Health, 2018)
Introduction: Breast cancer is a common problem and it is important to understand the beliefs that increase awareness of breast cancer and guide early diagnosis behaviors. This research is planned to examine the knowledge and fear levels of breast cancer along with the spiritual characteristics of nurses. Methods: This is a descriptive type research. The domain of the research consists of women nurses working in Health Sciences University Samsun Education and Research Hospital. Sampling was not undertaken, rather 327 nurses who were on duty between January and May of 2016 and were willing to cooperate were incorporated into the study. Data was collected by use of the survey forms, “Breast Cancer Fear Scale” and “Comprehensive Breast Cancer Knowledge Test (GKMBT).” Data were analyzed with SPSS 21 Software. Results: Nurses who participated in the research had an average of age of 32.27 ± 1.04 years, 60.6% of whom were married, and had an average duration of nursing practice of 12.49 ± 9.92. The nurses' breast cancer fear level point average was 26.11 ± 6.58, the GMKBT scale general information sub-dimension point average was 7.20 ± 2.81, the treatability sub-dimension point average was 5.80 ± 1.68, and the total point average was found out to be 12.87 ± 2.81. It was determined that nurses' knowledge levels of breast cancer were not related to fear levels. Conclusion: It was concluded that the nurses' breast cancer fear level was high and their knowledge level was moderate. In line with the results obtained, it might be recommended that studies should be made to increase the nurses' knowledge and awareness on breast cancer.